2016
DOI: 10.1007/s13538-016-0406-7
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Study of Surface Plasmon Resonance-based Fiber Optic Sensor Utilizing Cobalt and Nickel Films

Abstract: A surface plasmon resonance (SPR) based fiber optic sensor with cobalt (Co) and nickel (Ni) layers (one layer at a time) is theoretically analyzed. The sensitivity of sensor increases linearly with increase in refractive index of sensing medium for all thicknesses of Co and Ni layers. Besides it, SPR sensor with Co layer has been shown to demonstrate higher sensitivity than that of Ni layer. The usage of Co in place of noble metals (such as gold and silver) curtails the cost of SPR sensor. Optimized thicknesse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(11 citation statements)
references
References 23 publications
0
11
0
Order By: Relevance
“…The dielectric constant of nickel (Ni) is calculated from the Drude model, Here λ p and λ c are the plasma wavelength and collision wavelength of the metal. For Ni, λ p = 2.5381×10 -7 m and λ c = 2.8409×10 -5 m respectively (Shukla et al 2016). The refractive index of the host component (ZnO) at 633 nm is 1.98 (Kushwaha et al 2018).…”
Section: Theory Mathematical Modeling and Performance Parameter Of The Spr Biosensormentioning
confidence: 99%
See 1 more Smart Citation
“…The dielectric constant of nickel (Ni) is calculated from the Drude model, Here λ p and λ c are the plasma wavelength and collision wavelength of the metal. For Ni, λ p = 2.5381×10 -7 m and λ c = 2.8409×10 -5 m respectively (Shukla et al 2016). The refractive index of the host component (ZnO) at 633 nm is 1.98 (Kushwaha et al 2018).…”
Section: Theory Mathematical Modeling and Performance Parameter Of The Spr Biosensormentioning
confidence: 99%
“…Sarika Shukla et al analyzed fiber based SPR sensor utilizing cobalt and nickel layers as plasmonic materials. They suggested that the utilization of magnetic materials such as Co and Ni in place of noble metals such as gold and silver not only curtails the cost of the SPR sensor but greatly improved its sensitivity (Shukla et al 2016). Nisha et al (2019) recently reported that the hybrid structure consisting of Ni over Au with addition layer of 2D material MoS 2 on BK7 prism subsequently improved the sensitivity as high as 229°/RIU.…”
Section: Introductionmentioning
confidence: 99%
“…Nickel (Ni), a ferromagnetic metal, is also gaining interest due to its notable magneto-optical and magnetic properties and being a good light absorber. Using inert magnetic metals minimizes the cost of the SPR sensor while simultaneously considerably improving its performance [20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…So, the dielectric material (2D material) attracted significant interest due to its optical and mechanical properties for enhancement of sensitivity [19]. Ni as a plasmonic metal has been used due to its low cost to improve the sensitivity of SPR sensor [20]. Final layer in the structure design of SPR sensor is sensing medium which is also called as sensing analyte.…”
Section: Introductionmentioning
confidence: 99%